Flow Experiences in University Students - Ermiş, Ece Naz; Bayraktar, Seda (Elsevier, 2014)
The aim of this study is to investigate the flow experiences of university students. The research group consists of 35 students from the Istanbul Kültür University. Experience Sampling Method was used in the study. Each students completed 5 forms in 7 days. A total of 175 forms were included in the evaluation. By the results of the study, the concentration of students regarding the task their age and their department in university the difficulty levels in paying attention and the levels of feeling of control in themselves is different from each other.
Keywords: motivation; happiness; attention; willingness; flow theory